A software engineering environment for modeling and developing knowledge-intensive systems - Bruno, G.; Macario, G.; Grammatica, A. (Fourth International Conference on Software Engineering and Knowledge Engineering : proceedings, 1992)
One of the issues in current software engineering research is the formalization of the production of large-scale software systems. Basically, the knowledge about a production process relies on three models: the product, the organization and the process model. Product and organization models are information models: an extended entity-relationship formalism is suitable to build such models. On the other hand, process models are behavioral models which react to temporal events or to user actions on the repository. The authors' research aims at providing conceptual models which support the construction of rigorous and verifiable organization and process models. They have developed two formalisms: Quid for building E-R models and generating the corresponding repository, and Protob for expressing process models in terms of high level nets. This paper illustrates the formalisms and present examples of process models.< >